Repercussões da derivação gástrica em Y de Roux materna sobre o tecido adiposo marrom da prole masculina adulta - Ceglarek, Vanessa Marieli (2018)
Intake of a hypercaloric diet during gestation and lactation induces offspring obesity, an event that involves the programming of brown adipose tissue (BAT). Bariatric surgery (BS) is the fastest method of weight loss and restoration of energetic homeostasis in obese individuals, a procedure that could modulate the development of the fetus, if performed in the mothers, having effects on offspring in adult life. The maternal BS modulates the mother's BAT and prevents obesity in the offspring, but its impact on BAT offspring is unknown. In the present study, the histological and functional aspects of the BAT of first generation (F1) adults descended from obese mothers submitted to Roux-en-Y gastric bypass surgery (RYGB) were evaluated. To that end, we used the offspring of Wistar rats who received a high-calorie cafeteria diet (CAF) throughout life and at 65 days of life were submitted to False Operation (CAF-FO) or Roux-en-Y Gastric Bypass (CAF- RYGB) and the offspring of rats Controls (CTL), which received standard diet. At 30 days of age the offspring were weaned, the males were separated (n = 6 / group) and the groups of offspring (F1) nominated according to maternal treatment, generating 3 experimental groups: 1) CTLF1; 2) CAF-FO F1 and 3) CAF-RYGB F1. All the offspring received standard diet throughout life. At 120 days of age the offspring were euthanized, the BAT collected, and the histological and protein expression analyzes of the mitochondrial decoupling protein 1 (UCP1) and the electron transport chain (ETC) were performed. The CAFFO F1 BAT presented greater fat accumulation and adipocyte area, with a reduction in the expression of complex I (CI) and complex III (CIII) of the ETC in relation to the CTL F1 group (p <0.05). Animals from the CAF-RYGB F1 group showed increased cell proliferation, accompanied by reduction of fat stocks, increased expression of UCP1 in relation to CAF-FO F1 animals. The expression of IC and CIII in the BAT of these animals remained reduced in relation to the animals of the CTL F1 group. The present study shows that maternal CAF modulates the offspring BAT, favoring greater lipid deposition in BAT from adult offspring, contributing to elevated adiposity. Maternal RYGB can prevent obesity in adult offspring, probably by increasing the expression of UCP1, increasing energy expenditure.